2011
DOI: 10.1186/1471-2288-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with substantial heterogeneity in Cochrane reviews. Cross-sectional study

Abstract: BackgroundDealing with heterogeneity in meta-analyses is often tricky, and there is only limited advice for authors on what to do. We investigated how authors addressed different degrees of heterogeneity, in particular whether they used a fixed effect model, which assumes that all the included studies are estimating the same true effect, or a random effects model where this is not assumed.MethodsWe sampled randomly 60 Cochrane reviews from 2008, which presented a result in its first meta-analysis with substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 43 publications
1
132
0
Order By: Relevance
“…Heterogeneity was dealt with by sensitivity analysis, omitting one study at a time to detect interstudy bias, after which these were excluded. 39 The pooled estimates (pooled odds ratio) were obtained using the MantelHaenszel fixed-effect method. 50 BAC was dichotomized to negative and positive for the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity was dealt with by sensitivity analysis, omitting one study at a time to detect interstudy bias, after which these were excluded. 39 The pooled estimates (pooled odds ratio) were obtained using the MantelHaenszel fixed-effect method. 50 BAC was dichotomized to negative and positive for the analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Dealing with study heterogeneity is a complicated matter with no definitive solution. 39 We chose to deal with heterogeneity by using a fixed-effect method and omitting one study at a time to identify studies causing heterogeneity so these could be excluded for sensitivity analysis.…”
mentioning
confidence: 99%
“…21 Furman et al, 2003 22 Heller et al, 2007 18 Maayan-Metzger et al, 2012 23 Manzoni et al, 2013 17 12 8,12 A randomeffects model for conducting metaanalysis has been suggested as a reasonable way of addressing heterogeneity in pooled studies, and in such cases narratively explaining the reasons for heterogeneity has been proposed. 38 We justify using our meta-analysis approach on the basis of these methodological suggestions.…”
Section: Figurementioning
confidence: 99%
“…The random effects model assumes that the effects in the different models follow a distribution, and confidence intervals combine between-study and within-study variances. 12 The outcomes of intrao perative variables, donor surgical complications and graft-related urologic complications, delayed graft function, and graft loss in the recipients were summarized using means and 95% confidence intervals.…”
Section: Statistical Analysesmentioning
confidence: 99%